2012
DOI: 10.5937/ekonhor1201013m
|View full text |Cite
|
Sign up to set email alerts
|

Analiza elemenata kvaliteta usluga u korporativnom bankarstvu

Abstract: Fokusiranost na potrošače poslednjih godina doživljava ekspanzij u u uslužno orij entisanim delatnostima, uključujući i banke. Potrebe korisnika fi nansij skih usluga dinamično se menjaju, zbog čega je neophodno da banke razvij aju dugoročne poslovne odnose sa svojim klij entima, kako bi postale i ostale profi tabilne. Cilj ovog istraživanja usmeren je na ispitivanje stavova korporativnih klij enata -malih i srednjih preduzeća -o različitim elementima kvaliteta usluga, koje pružaju bankarske institucij e. Rezultati r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…Younger consumers consider the lack of face-toface contact to be less important, in comparison to older clients. On the other hand, a lower degree of face-to-face contact that is typical for the electronic banking field is the basis for maintaining strong relationships with clients (Marinković, Obradović, 2012). Howcroft et al (2002) conducted a research which also found that the level of education does not affect the use of electronic banking.…”
Section: Demographic Profile Of Users Of Electronic Bankingmentioning
confidence: 99%
See 2 more Smart Citations
“…Younger consumers consider the lack of face-toface contact to be less important, in comparison to older clients. On the other hand, a lower degree of face-to-face contact that is typical for the electronic banking field is the basis for maintaining strong relationships with clients (Marinković, Obradović, 2012). Howcroft et al (2002) conducted a research which also found that the level of education does not affect the use of electronic banking.…”
Section: Demographic Profile Of Users Of Electronic Bankingmentioning
confidence: 99%
“…Accordingly (Garvin, 1984), concludes that quality lies in the eye of the beholder. Specifically, the elements that include habits, attitudes, experiences, value set or social class of an individual are just some of the factors that determine the manner in which a person can perceive quality (Marinković, Senić, 2012).…”
Section: Quality Of Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Parasuraman et al (1985) observe the service quality from the customer's point of view, and compare their expectations with the perception of delivered service. The quality service represents one of the most important ‗triggers' of customer's loyalty and generates wide scope of interests among researchers and practitioners (Marinković & Senić, 2012).…”
Section: Review Of Literature 21 Tourism Multiplier Effect As Exempmentioning
confidence: 99%
“…Research of Zelenović et al (2017) showed that clients expect much more from banks in terms of service quality compared to the quality that is provided to them, which points to the need for further research to determine whether and in which segments there is a lack of fulfillment of client expectations and the possibility of improving the service quality which banks are providing. Also, Marinković and Senić (2012) state that it would be desirable to examine the influence of the service supply factors of banks on customer loyalty. According to the author's knowledge, the researches that deal with the analysis of the effects of banking services quality dimensions on clients' satisfaction and loyalty in Serbia are very rare, and taking into account this fact, as well as the previously noted findings, research gap that needs to be supplemented with new knowledge has been identified.…”
Section: Introductionmentioning
confidence: 99%